2009
DOI: 10.1242/jcs.042754
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ceramide glucosyltransferases, which are essential for glycosphingolipid synthesis, is only required in a small subset ofC. eleganscells

Abstract: Glycosphingolipids (GSLs) are glycosylated derivatives of ceramide in the lipid bilayer. Their ubiquitous distribution and complexity suggest that they have important functions, but what these are in vivo is still poorly understood. Here, we characterize the phenotype of Caenorhabditis elegans mutants with essentially no GSLs. The C. elegans genome encodes three ceramide glucosyltransferase (CGT) genes, which encode enzymes required for GSL biosynthesis. Animals lacking CGT do not synthesize GSLs, arrest growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 59 publications
2
52
0
Order By: Relevance
“…Recently, it has been reported that ceramide glucosyltransferase genes involved in the biosynthesis of glycosphingolipids are strongly expressed in the pharyngeal-intestinal valve and in a small group of cells in the tail (37), similar to LEC-8::EGFP expression. It is also of interest how LEC-8 might function cooperatively with glycosphingolipids in those cells in C. elegans.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, it has been reported that ceramide glucosyltransferase genes involved in the biosynthesis of glycosphingolipids are strongly expressed in the pharyngeal-intestinal valve and in a small group of cells in the tail (37), similar to LEC-8::EGFP expression. It is also of interest how LEC-8 might function cooperatively with glycosphingolipids in those cells in C. elegans.…”
Section: Discussionmentioning
confidence: 93%
“…Dashes indicate no phenotype reported. 1 (Liu et al, 2014); 2 (Menuz et al, 2009); 3 (Deng et al, 2008); 4 ; 5 ; 6 (Mendel et al, 2003); 7 (Lin et al, 1998); 8 (Gulbins et al, 2013); 9 (Kim and Sun, 2012); 10 (Marza et al, 2009); 11 (Zhang et al, 2011).…”
Section: Elegans Serine Palmitoyltransferase (Spt)mentioning
confidence: 99%
“…In contrast to mammals and flies, which synthesize a single CGT protein, the C. elegans genome encodes three CGT proteins: CGT-1, CGT-2 and CGT-3 (Ichikawa and Hirabayashi, 1998;Leipelt et al, 2001). All CGTs generate glucosylceramide (GlcCer), the precursor of all C. elegans GSLs with CGT-3 possessing the highest enzymatic activity (Leipelt et al, 2001;Marza et al, 2009;Nomura et al, 2011). Double knock-down of cgt-1;cgt-2 by RNAi reduced overall enzymatic activity by 40%, whereas cgt-1;cgt-3 or cgt-2;cgt-3 double RNAi knock-down reduced enzymatic activity by 86% each (Nomura et al, 2011).…”
Section: Ceramide Glucosyltransferase (Cgt) In C Elegans Developmentmentioning
confidence: 99%
“…Knockout and/or knockdown of UGCG are lethal in mouse, Drosophila, and C. elegans, indicating a crucial role for GlcCer and GSLs synthesized from GlcCer during embryogenesis [35,36,52,53]. Ugcg knockout mice die in utero, because gastrulation is blocked by ectodermal apoptosis [53,54].…”
Section: Functions Of Glccermentioning
confidence: 99%
“…Three UGCG genes exist in C. elegans. Knockdown of all three UGCG genes causes growth arrest at the first larval stage [52]. It was recently identified using a global C. elegans tubulogenesis screening assay that UGCG is a critical enzyme for epithelial polarity [56].…”
Section: Epithelial Glccer In Cell Polaritymentioning
confidence: 99%